1994
DOI: 10.1530/jrf.0.1010563
|View full text |Cite
|
Sign up to set email alerts
|

Function and culture requirements of snow leopard (Panthera uncia) spermatozoa in vitro

Abstract: Electroejaculates from eight snow leopards were used to determine how the motility of spermatozoa was influenced by (i) type of media (Ham's F10, PBS, human tubal fluid or RPMI-1640); (ii) holding temperature (23 degrees C versus 37 degrees C); (iii) washing of spermatozoa and (iv) a sperm metabolic enhancer, pentoxifylline. The duration of sperm motility was assessed by evaluating samples in each treatment every hour for 6 h and a sperm motility index (a value combining percentage sperm motility and rate of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 8 publications
0
19
1
Order By: Relevance
“…; n = 8. Results demonstrate that (a) PBS enhances (P < 0 05) sperm motility overall compared with Ham's F10 (data adapted from Roth et al 1994) and (b) sodium bicarbonate supplementation to PBS has a profound detrimental effect on sperm motility. cheetah (Donoghue et al 1992b), tiger (Donoghue et al 1992c) and clouded leopard ) are capable of binding and penetrating both the outer and inner layers of the domestic cat zona in vitro.…”
Section: Importance Of Species Specificity To the Wildlife Spermatolomentioning
confidence: 94%
See 2 more Smart Citations
“…; n = 8. Results demonstrate that (a) PBS enhances (P < 0 05) sperm motility overall compared with Ham's F10 (data adapted from Roth et al 1994) and (b) sodium bicarbonate supplementation to PBS has a profound detrimental effect on sperm motility. cheetah (Donoghue et al 1992b), tiger (Donoghue et al 1992c) and clouded leopard ) are capable of binding and penetrating both the outer and inner layers of the domestic cat zona in vitro.…”
Section: Importance Of Species Specificity To the Wildlife Spermatolomentioning
confidence: 94%
“…It is interesting that snow leopard spermatozoa from high quality electroejaculates abruptly lose motility in Ham's F10 (Fig. 8a) (Roth et al 1994). In contrast, snow leopard spermatozoa exposed to simple phosphate-buffered saline (PBS) sustain a higher (P < 0 • 05) sperm motility index profile in vitro for at least 6 h. This unique medium preference indicates a species-specific sensitivity not observed among other felids studied to-date.…”
Section: Importance Of Species Specificity To the Wildlife Spermatolomentioning
confidence: 99%
See 1 more Smart Citation
“…Captive snow leopards have been successfully immobilized with tiletamine-zolazepam (TZ; Roth et al, 1994), medetomidine (MED)-ketamine (Jalanka, 1989a), and a combination of xylazine and ketamine (Jalanka, 1989b). The three field studies that involved multiple immobilizations of wild snow leopards employed ketamine (Jackson, 1996), a combination of medetomidine and ketamine (Oli, 1997), and tiletamine-zolazepam (McCarthy et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some researchers have reported successful semen collection from wild felids by using electroejaculation, such as tigers (Panthera tigris- Donoghue et al, 1992), snow leopards (Panthera uncia- Roth et al, 1994), Indian leopards (Panthera pardus- Jayaprakash et al, 2001), caracals (Caracal caracal- Pope et al, 2001), jaguars (Panthera onca- Morato et al, 2001;Silva et al, 2003), ocelots (Leopardus pardalis- Queiroz et al, 2002), margays (L. wiedii) and tigrinas (L. tigrinus- Morais et al, 2002). Graham et al (1978) reported the use of electroejaculation to collect semen from nondomestic felids.…”
Section: Electroejaculationmentioning
confidence: 99%